AB0951 Preclinical Atherosclerosis in Patients with Ankylosing Spondylitis without Clinically Evident Cardiovascular Disease. (10th June 2014) - Turhanoglu, A.D.; Ustun, N.; Kurt, M.; Yagiz, A.E.; Guler, H.
Abstract : Background: Ankylosing spondylitis is a chronic sistemic inflammatory sistemic disease. An increase in cardiovascular mortality and morbidity is reported in ankylosing spondylitis (AS). However, the association between atherosclerosis and AS is still debated. Objectives: The primary objective of the present study was to identify pre-clinical atherosclerosis in the patients with AS by measuring carotid intima media thickness (CIMT), arterial stiffness index (ASI) and epicardial fat thickness (EFT). The secondary objective of the present study was to investigate the relationships between these parameters and disease activity/mobility indices. Methods: We studied 26 patients with AS without clinically evident cardiovascular disease, and 26 age-, sex- and BMI- matched healthy controls. Disease activity was evaluated by Bath AS disease activity index (BASDAI). Mobility was measured by Bath AS metrology index (BASMI). CIMT was measured by high-resolution B-mode ultrasound. Measurements of the ascending aorta were performed in the 2D parasternal long axis view at 3 cm above the aortic valve. The EFT was measured on the free wall of the right ventricle from the parasternal long-axis view. Results: There were no significant differences in baseline demographic characteristics (age, sex, BMI) and cardiovascular risk factors (current smokers, systolic blood pressure, diastolic blood pressure, heart rate, C-reactive protein level) between the patients and the controls. CIMT was significantly higher observed in AS patients (0.70±0.16 mm vs. 0.60±0.10 mm; p=0.012). ASI was significantly higher in AS group (14.2±10.8 vs. 8.6±3.1, p=0.018). EFT was significantly increased in AS patients (5.15±1.13 mm vs 4.11±1.22 mm, p=0.003). There was no significant correlation between these parameters and AS indices (BASDAI, BASMI) (p>0.05). Conclusions: In this study, a significantly increased carotid IMT, arterial stiffness and epicardial fat thickness, markers of sub-clinical atherosclerosis, were observed in AS patients compared with healthy controls. There was no significant correlation between these cardiovascular parameters and disease activity/mobility indices. References: Lautermann D. Ankylosing spondylitis-cardiac manifestations. Clin Exp Rheumatol 2002;20 Suppl 28:11–5. Symmons DP. Men with ankylosing spondylitis have an increased risk of myocardial infarction. Arthritis Rheum 2004;50:477. O'Leary DH, Polak JF, Kronmal RA, Manolio TA, Burke GL, Wolfson SK Jr. Carotid artery intima and media thickness as a risk factor for myocardial infarction and stroke in older adults. Cardiovascular health study collaborative research group. N Engl J Med 1999;340:14–22. Iacobellis G, Assael F, Ribaudo MC, et al. Epicardial fat from echocardiography: a new method for visceral adipose tissue prediction. Obes Res 2003;11:304-10. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1959